Empowerment of Disabled Individuals through CSR Program of Pertamina Inc. TBBM Boyolali to Realize SDGs - Malik, Abdul; Alauddin, Murni Ratna Sari; Aditya, Rahadiyand (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2025)
Disability theory encompasses diverse approaches, including socio-political, materialist, cultural, and poststructuralist perspectives, challenging traditional medical models and emphasizing social causes and implications of disablement. This research examines the process and results of empowering disabled people through Pertamina Inc. Boyolali BBM Terminal's CSR program, which aims to realize Sustainable Development Goals (SDGs). The program has been implemented since 2018, providing batik and sewing training to disabled individuals in Boyolali district. The research uses a qualitative descriptive approach, collecting data through document analysis. The results show that the empowerment process has economically, psychologically, and socially benefited disabled people, enabling them to meet their needs, gain self-confidence, and overcome social stigma. The program's success is also reflected in the participants' annual turnover of 50 million. This achievement supports the realization of SDGs, particularly in reducing poverty, promoting healthy and prosperous lives, ensuring decent work and economic growth, and reducing inequality. The study concludes that the CSR program's empowerment process, which provides skills training, has been highly beneficial and contributes to achieving SDGs. The research recommends that State-owned companies and other companies should prioritize empowering more disabled people, as their numbers remain significant and have not been adequately covered by CSR programs.